MICROENVIRONMENT OF INTESTINAL ANASTOMOSES WITH COMPARATIVE ASSESSMENT OF IMMUNE STATUS IN PATIENTS WITH SMALL INTESTINE ANASTOMOSES - Tymchenko, M.Ye.; Ivanova, Yu.V.; Gramatiuk, S.M.; Zarutskyi, Ya.L.; Bilyi, V.Ya. (World of Medicine and Biology, 2020)
The purpose of the study was to assess local immune status as a marker for the risk of intestinal anastomosis failure. The research was based on the study of local immune mechanisms of intestinal anastomoses failure in the comparative aspect. The material of the study was the anastomosis tissue, areas of the intestine at a distance of 1-3 cm from the anastomosis, as well as the patients’ blood samples taken before surgery, on the first and the fifth days after the formation of the anastomosis in subgroups of the study. The occurrence of intestinal anastomoses failure is mainly determined by the interaction of immunocompetent cells and products of their activity - cytokines. Immunological disorders in the intestine tissues in the anastomosis area cause the failure pathogenesis. The microenvironment of intestinal anastomoses by immunological parameters is a field that promotes further progression of inflammation or serves as a buffer zone that protects tissue from pathological changes. The study revealed the formation of secondary immune deficiency in patients with resection of intestinal segments; recovery of immune status indices in patients with uncomplicated postoperative period occurs at an earlier date and to the fuller extent.
Keywords: intestinal anastomoses; failure; immunology